2020
DOI: 10.1016/j.trsl.2020.03.012
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome and frailty

Abstract: The human microbiome is constituted by an extensive network of organisms that lie at the host/ environment interface and transduce signals that play vital roles in human health and disease across the lifespan. Frailty is a critical aging-related syndrome marked by diminished physiologic reserve and heightened vulnerability to stress, predictive of major adverse clinical outcomes including death. While recent studies suggest the microbiome may impact key pathways critical to frailty pathophysiology, direct eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 330 publications
(399 reference statements)
0
16
0
Order By: Relevance
“…Impairment of the microbiota–gut–brain axis has been associated with several disorders, including neuropsychiatric diseases. Hence, mounting evidence supports the hypothesis that gut microbiome dysbiosis is implicated in the onset of cognitive impairment and frailty [ 10 , 24 , 26 ]. Furthermore, recent studies proposed inflammaging as a critical component in the onset and progression of frailty and demonstrated that the gut microbiota becomes pro-inflammatory over time during aging [ 10 ].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Impairment of the microbiota–gut–brain axis has been associated with several disorders, including neuropsychiatric diseases. Hence, mounting evidence supports the hypothesis that gut microbiome dysbiosis is implicated in the onset of cognitive impairment and frailty [ 10 , 24 , 26 ]. Furthermore, recent studies proposed inflammaging as a critical component in the onset and progression of frailty and demonstrated that the gut microbiota becomes pro-inflammatory over time during aging [ 10 ].…”
Section: Introductionmentioning
confidence: 94%
“…Frailty is a multisystem dysregulation leading to decreased physiological reserve [ 8 , 9 ]. Thus, frailty is related to aging, but it does not reflect chronologic age, showing big heterogeneity among subjects [ 10 ]. The age-related frailty is principally associated with phenotypic and/or locomotor impairment, both in humans and in animal models [ 8 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A popular but perhaps simplistic explanation for these effects emphasizes increased intestinal permeability in older people 135 . Increased gut permeability is associated with inflammageing, frailty and insulin resistance 67 , 136 . However, a polyphenol-based pilot intervention found that the age-linked beneficial effects included changes in the microbiome 129 .…”
Section: Microbiome-based Ageing Interventionsmentioning
confidence: 99%
“…The microbiome of elderly (around 80 y) dialysis patients might have developed a certain robustness and resistance to drastic environmental changes. Many studies address the effects of aging and immune senescence on the human microbiome 20 . Several changes in microbiome structure have been reported to occur with late age, including a reduction in microbiome diversity and increased inter-individual variation.…”
Section: Discussionmentioning
confidence: 99%
“…2 , right). Furthermore, in older adults, a reduction in those commensal bacteria that have a beneficial function for the host, such as maintaining mucus production and the integrity of the mucosal barrier, is observed on the one hand, and an emergence of pathobionts on the other 20 . However, the microbiome of elderly dialysis patients is definitely under-investigated 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%